2023
DOI: 10.1097/rlu.0000000000004954
|View full text |Cite
|
Sign up to set email alerts
|

Enterovesical Fistula in a Lymphoma Patient Revealed by FDG PET/CT With an Oral Contrast Agents

Linlin Guo,
Guohua Shen

Abstract: A 60-year-old man with colonic diffuse large B-cell lymphoma was referred for FDG PET/CT for initial staging. He was suspected of enterovesical fistula. After oral administration, large amounts of contrast agents accumulated in the bowel lumen and leaked into the bladder through a well-marked fistulous tract. Corresponding to the fistula, a linear pattern of FDG uptake extended from the bladder into the colonic lumen, and the measured SUVmax inside the lesion was as high as that of the urinary bladder. Cystogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the case of positive oral contrast media, several studies have demonstrated an improvement in digestive distension which was a potential help for diagnosis ( 61–63 ), but few have been able to demonstrate a clinical benefit. Chen et al reported a more accurate delayed PET/CT with laxative-augmented contrast medium than conventional PET/CT for the evaluation of colorectal foci ( 64 ) and Guo et al reported a case of enterovesical fistula revealed with oral contrast ( 65 ). The main challenge in assessing the impact of oral contrast agents was the hyperfixation of digestive structures ( 66 ), particularly due to distension, increased motility, and irritative phenomena ( 30 ).…”
Section: Clinical Added Value Of Cepet/ctmentioning
confidence: 99%
“…In the case of positive oral contrast media, several studies have demonstrated an improvement in digestive distension which was a potential help for diagnosis ( 61–63 ), but few have been able to demonstrate a clinical benefit. Chen et al reported a more accurate delayed PET/CT with laxative-augmented contrast medium than conventional PET/CT for the evaluation of colorectal foci ( 64 ) and Guo et al reported a case of enterovesical fistula revealed with oral contrast ( 65 ). The main challenge in assessing the impact of oral contrast agents was the hyperfixation of digestive structures ( 66 ), particularly due to distension, increased motility, and irritative phenomena ( 30 ).…”
Section: Clinical Added Value Of Cepet/ctmentioning
confidence: 99%